Decision to convene shareholders meeting - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In view of convocation of shareholders meeting one needs to differ making of decision to convene shareholders meeting and convocation alone. Resolution of authorized company body to convene shareholders meeting is juridical act. When legal nature of informing or convocation is in question, one should take into consideration the fact that it does not have character of juridical act.